Analysis of Complications of Laparoscopic Procedures in Urology - Malik Adil Mehmood, Rafiullah, Numan Alam, Rizwan Ullah, Nadeem Ahmed Shaikh, Kausar Anwar, Muhammad Ahsan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Laparoscopic procedures have revolutionized the field of urology by offering minimally invasive alternatives to traditional open surgeries. Objectives: The main objective of the study is to find the complications of laparoscopic procedures in urology Material and methods: This retrospective observational study was conducted at institute of kidney disease Hayatabad Peshawar, to comprehensively analyze the complications arising from laparoscopic procedures in urology conducted between the years 2022 and 2023. Results: A total of 320 patients who underwent laparoscopic urological procedures between 2022 and 2023 were included in the study. The mean age of the cohort was 54.8 years (± 10.2), with a range of 28 to 76 years. Of the participants, 215 (67.2%) were male and 105 (32.8%) were female.Postoperative complications occurred in 92 patients (28.8%). The Clavien-Dindo classification was utilized to categorize the severity of complications. Grade I complications, defined as any deviation from the normal postoperative course without the need for pharmacological treatment or surgical intervention, were observed in 34 cases (10.6%). Practical Implication: This study will help in intraoperative and postoperative issues emphasize the need for precise techniques and vigilant postoperative care. Conclusion: It is concluded that varying rates of intraoperative and postoperative issues emphasize the need for precise techniques and vigilant postoperative care. Tailored approaches based on surgical techniques and patient age can enhance outcomes, reinforcing the importance of thorough evaluation and comprehensive management. Keywords: Postoperative, Patients, Laparoscopic, Urology, Procedures, Operative